Development of the Modified Strategic Management Accounting Disclosure Index (MoSMADi) for Companies’ Decision-Making, Control and Monitoring of Business Strategies in Attaining Business Sustainability - James, Bernadette Josephine; Joseph, Corina; Said, Roshima (The journal of contemporary issues in business and government, 2023)
The paper aims to explain the development of the modified strategic management accounting disclosure index. The main purpose of strategic management accounting information is to support companies’ decision-making, control, and monitoring of business strategies to attain business sustainability. The Modified Strategic Management Accounting Disclosure index which consists of 70 items aims to serve as a holistic and comprehensive checklist to evaluate the extent of strategic management accounting information disclosure on companies’ annual reports. It is hoped that the modified strategic management accounting disclosure index would enhance the level of strategic management accounting information disclosure by companies as the checklist is developed based on international and national criteria to highlight the benefits of having the index. The purpose of developing this index is to provide a coherent framework to ensure business sustainability and the need for strategic management accounting information for decision-making, control, and monitoring of the company’s strategies in pursuit.